Engineered terahertz emission from spintronic heterostructures: amplitude, phase and chirality - Agarwal, Piyush (Nanyang Technological University, 2023)
The terahertz field ranges from 0.1THz to 30THz in the electromagnetic spectrum and has attracted significant attention from the scientific community due to its several demonstrated applications in material characterization, fault imaging, biomedical diagnosis, 6G communications, and ultrafast data processing. In particular, future data processing is envisioned to be driven by ultrafast spin transport electronics, which lies in the terahertz frequencies having a three-order advancement to the present operational frequency. The methods exploit spins' inherent properties to achieve non-volatile, low-power, and faster processes than conventional electronics. Besides, the recent advances in controlling the spins at terahertz frequencies have supported the pursuit to reveal a promising future for terahertz spintronic devices. The underlying mechanism of the spintronic terahertz emitter is driven by the femtosecond pulse excitation of the ferromagnet(FM)/ heavy metal(HM) heterostructure. As such, the photoexcitation leads to ultrafast spin-scattering events in the FM, during which the spins transport from the FM into the adjacent heavy metal(HM) layer to experience an inverse spin Hall effect, producing a transverse charge current and terahertz radiation. The processes have thus unveiled a novel research avenue in ultrafast science, along with introducing several exploratory grounds. This thesis aims to identify and answer a few of them by unveiling efficient spin manipulation methods. The main findings of the thesis are divided into two parts. The first part covers three chapters, 4, 5, and 6, with a focus on revealing device applications within the conventional ferromagnet/heavy metal spintronic heterostructure. In chapter 4, we begin with an elementary question to interpret the relationship between the magnetization of a ferromagnet and the generation of terahertz frequencies. Therefore, we measured the amplitude of the THz pulse while sweeping the external magnetic field and demonstrated a hysteresis-like loop. Its comparison with the M-H loop measured using the vibrating sample magnetometer showed a remarkable similarity, suggesting THz amplitude to scale proportionally with the magnetization of FM. We reveal that the phenomenon stems due to the exchange interaction between the localized d-electrons and conduction s-electrons in the ferromagnet. Chapter 5 exploits the photo-thermal effects on the transport spin currents arising from the FM. Femtosecond photoexcitation is known to perturb the electronic temperature of FM in subpicosecond timescales. We demonstrated that due to the electron-phonon heat thermalization, the lattice experiences an abrupt decrease in magnetic anisotropy within a few picoseconds, 10 which cause an ultrafast shrink in magnetic coercivity. The results thus revealed an ultrafast route for amplitude and phase manipulation of generated spin current. In practical devices, spin systems have become a potential candidate for memory applications because of their magnetic field-sensitive anisotropic energy. However, such ultrafast spintronic emitters lacked an active platform for realizing an electric-field control. In chapter 6, we, therefore, coupled a piezoelectric substrate with a ferromagnet and introduced magnetoelectric effects in the system. An electric-field controlled terahertz spin current thus demonstrated a giant ~270% spin amplitude modulation with an additional route for electric-field control of the phase. The second part of the thesis (chapters 7, 8, and 9) focus on the fundamental spinexcitation processes. In chapter 7, we investigated the spin current generation in the standard FM/HM heterostructure and established a detailed underlying mechanism of photoexcitation. The study highlighted that an excited non-polarized spin current generation from the HM can excite the FM for the second time, apart from FM's primary photoexcitation. A comprehensive measure of the energy transfer from heavy metal to ferromagnet at an ultrafast time scale was explored to explain the overall superdiffusive spin transport processes. Another factor that governs the efficient spintronic terahertz emission is the fundamental spin-to-charge conversion; however, it has approached saturation due to the limited library of heavy metals. In chapter 8, we revealed that an underexplored FM-HM interface effect holds the potential to produce a significant spin-to-charge conversion close to that of the best spin-Hall conductive material (Platinum). The study unlocks a path for a broad class of materials, including topological insulators, Weyl semimetals, and two-dimensional semiconductors, for accessing enhanced interfacial effects. To conclude, in chapter 9, we highlight that control over the intensities and polarization of the THz waves has produced several efficient sensors and reconfigurable devices in the past. Despite of which, it lacked the desired chirality control of the broadband THz field. By using the spintronic terahertz emitters, we demonstrated a route to produce a pair of transverse THz waves. The pair of THz waves were generated from synthetic antiferromagnetic layers, which upon experiencing differential spin relaxation times, yield a chiral THz emission. The results presented a unique application of relaxation asymmetry for use in encoding and encrypting information through chiral THz waves. To summarize, the thesis aims to contribute to the synergies of spintronics and photonics for advanced applications in developing scalable devices bearing low-cost fabrication with on-chip compatibility.